(untitled) (Scientific journal of the Fergana State University, 2023)
This article describes the artistic figurative language and its theoretical basis, it is used in the epic of the great poet Alisher Navoi “Lison ut-Tair” (The Language of The Birds) and samples for the metaphor, which is one of the types of artistic figurative tools are commented on. The purpose of the study is to investigate the scope of use of artistic visual tools in the epic “Lison ut tair”. The method of research is the method of analysis, identifying the descriptive tools in the prose narrative of the epic and dividing them into types: metaphor, metonymy, exaggeration. As a result of the research, figures of the language were extracted and analyzed. The types of tropes were identified, their use, synonymy and homonymous phenomena were determined. Visual means were theoretically studied, and samples in the work were scientifically researched.